2012
DOI: 10.4085/1062-6050-47.2.178
|View full text |Cite
|
Sign up to set email alerts
|

Limb Blood Flow After Class 4 Laser Therapy

Abstract: Laser therapy at the 3-W (360-J) dose level was an effective treatment modality to increase blood flow in the soft tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 29 publications
2
22
0
1
Order By: Relevance
“…This study also demonstrated positive responses of the previous LED application in the blood lactate disappearance capacity; these effects could be due the improvement in microcirculation [6,29] and also because of a decreased lactate production with prior application of light by modifications on oxidative capacity through enzymatic, mitochondrial, and systemic changes, facilitating the resynthesis of ATP by the alactic pathway [20,21,29]. Although there was no difference between conditions for LA peak , LED condition presented higher removal capacity compared to PLA, with significantly lower values of LA 13-min and LA 15-min .…”
Section: Discussionsupporting
confidence: 61%
“…This study also demonstrated positive responses of the previous LED application in the blood lactate disappearance capacity; these effects could be due the improvement in microcirculation [6,29] and also because of a decreased lactate production with prior application of light by modifications on oxidative capacity through enzymatic, mitochondrial, and systemic changes, facilitating the resynthesis of ATP by the alactic pathway [20,21,29]. Although there was no difference between conditions for LA peak , LED condition presented higher removal capacity compared to PLA, with significantly lower values of LA 13-min and LA 15-min .…”
Section: Discussionsupporting
confidence: 61%
“…A relatively novel treatment option in equine medicine is high-power laser therapy. In human medicine this therapy has been successfully used to address multiple orthopedic pathologies (4)(5)(6)(7). In a single blinded randomized clinical study in human Achilles tendinopathy, highpower laser therapy significantly reduced pain (8).…”
Section: Introductionmentioning
confidence: 99%
“…Investigators [4][5][6][7] have begun to explore the ergogenic effects of NIR light therapy in reducing skeletal muscle fatigue and attenuating strength loss during and after resistance exercise. Previous authors [8][9][10] have provided evidence for the ability of light therapy to enhance blood circulation, resulting in an increase in tissue oxygenation. Increasing circulation in the irradiated tissue can lead to enhanced oxygen and substrate delivery, thereby improving the overall ability of the muscle to perform work.…”
mentioning
confidence: 99%